2006
DOI: 10.1016/j.colsurfb.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic features of Bacillus cereus cell surfaces with biosorption of Pb(II) ions by AFM and FT-IR

Abstract: In order to elucidate the potential mechanisms involved in the biosorption of metal ions, atomic force microscopy (AFM) and Fourier transform infrared (FT-IR) spectroscopy were used to characterize the interaction between Pb 2+ and Bacillus cereus. AFM imaging of the biomass surfaces exposed to different concentrations of lead ions solution showed a major morphological change occurred after Pb 2+ biosorption. The FT-IR spectra indicated the binding characteristics of the lead ions involved the carboxyl, hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 51 publications
10
34
0
1
Order By: Relevance
“…The observed fast biosorption kinetics was consistent with the biosorption of metal involving non-energy mediated reactions, where metal removal from solutions is due purely to physico-chemical interactions between biomass and metal solution. This fast metal uptake from solution indicates that binding might have resulted from interaction with functional groups on the cell wall of the biosorbent rather than diffusion through the cell wall of the biomass this is in agreement with results that have been reported in many studies using different biosorbents on the uptake of different heavy metals (Kumar et al, 2006;Pan et al, 2006;Bueno et al, 2008). The fitting of data to Redlich-Peterson, Sips, Langmuir and Freundlich isotherms suggest that biosorption of Pb (II) ions onto the biosorbent could be explained by Redlich-Peterson isotherm with correlation coefficient of 0.8218 as outlined in (Hall et al, 1996;Ozer and Ozer, 2003), it may be suggested that biosorption takes place as monolayer phenomena and that L. cylindrica biomass was not fully covered by the metal ions.…”
Section: Resultssupporting
confidence: 80%
“…The observed fast biosorption kinetics was consistent with the biosorption of metal involving non-energy mediated reactions, where metal removal from solutions is due purely to physico-chemical interactions between biomass and metal solution. This fast metal uptake from solution indicates that binding might have resulted from interaction with functional groups on the cell wall of the biosorbent rather than diffusion through the cell wall of the biomass this is in agreement with results that have been reported in many studies using different biosorbents on the uptake of different heavy metals (Kumar et al, 2006;Pan et al, 2006;Bueno et al, 2008). The fitting of data to Redlich-Peterson, Sips, Langmuir and Freundlich isotherms suggest that biosorption of Pb (II) ions onto the biosorbent could be explained by Redlich-Peterson isotherm with correlation coefficient of 0.8218 as outlined in (Hall et al, 1996;Ozer and Ozer, 2003), it may be suggested that biosorption takes place as monolayer phenomena and that L. cylindrica biomass was not fully covered by the metal ions.…”
Section: Resultssupporting
confidence: 80%
“…Different biosorbents used for the adsorption of various heavy metals yielded similar observations. For example, in a study conducted by Abu Al-Rub and fellow researchers using C. vulgaris algal cells, a substantial viable biomass remained after biosorption of less concentrated copper solutions (0.1 g/ℓ than in the case of highly concentrated copper solutions (20 g/ℓ) (Kumar et al, 2006;Fiol et al 2006;Abu Al-Rub et al, 2006, Pan et al, 2006.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…Extensive washing of biosorbent with distilled water was carried out to remove any unreacted chemical [7].…”
Section: Pretreatment Of Biosorbentsmentioning
confidence: 99%
“…Physical pretreatment method such as heat, autoclaving, glacial, ventilation and baking and substance pretreatment by means of alkali and organic chemicals showed improvement and diminution in metal bioadsorption, [7] Trapa natans fruit belonging to the family Trapaceae, its root is fine long and many in number, leaves are triangular, fan shaped. Trapa natans are nut like and one to two inches in diameter.…”
Section: Introductionmentioning
confidence: 99%